Pathways from Community-Based Tourism to Poverty Reduction: A Multilevel Mediation Analysis in Vietnam - Minh, Hieu Nguyen; Khanh, Cuong Le; Huu, Duc Luu; Quoc, Viet Truong; Manh, Hai Nguyen; Thi, Thuong Vu; My, Trang Do Thi (Journal of Cultural Analysis and Social Change, 2025)
Community-based tourism (CBT) is increasingly viewed as a viable strategy for sustainable poverty reduction, yet rigorous empirical evidence remains scarce. This study investigates the causal impact of CBT on multidimensional poverty across 63 Vietnamese provinces from 2015 to 2023 using a comprehensive panel dataset. Employing fixed effects models, instrumental variable estimation, and dynamic system GMM, we identify robust effects of CBT on household welfare. Results show that higher CBT intensity reduces provincial poverty rates by approximately 2.3–2.8 percentage points and increases household income by 15–18%. Mediation analysis demonstrates that these impacts operate primarily through employment creation, skill development, and infrastructure improvement. The effectiveness of CBT, however, varies substantially across regions, with stronger impacts observed in mountainous and coastal areas. Governance quality and community participation significantly moderate the CBT–poverty relationship, amplifying its poverty-reducing effect in provinces with stronger institutions and more inclusive participation. The findings provide new causal insights into the pathways through which CBT contributes to poverty alleviation and offer policy recommendations for designing sustainable, community-centered tourism strategies in emerging economies.